“Vulneración del doble conforme en materia penal en Ecuador. Análisis de los criterios jurisprudenciales emitidos por la Corte Constitucional” - Morales Riofrío, David Alejandro (2025)
To the reader, this work is based on a detailed analysis of the rulings issued by the Constitutional Court of Ecuador: No. 987-15-EP/20, No. 1965-18-EP/21, and No. 8-19-IN/21, related to the right to double conformity. The objective is to establish the progress this legal figure has achieved at the national level and to identify the circumstances that have led to its violation within the Ecuadorian context. In this regard, the study examines the jurisprudential criteria issued by the Constitutional Court regarding the protection of the presumption of innocence of individuals subject to criminal proceedings. This analysis considers the development of double conformity at both the international and domestic levels, detailing its characteristics and significant aspects that contribute to understanding this institution and distinguishing it from the appeal for review. For this purpose, the study first provides a brief conceptual and doctrinal description of the referred right. The research identifies the particularities of double conformity and contrasts them with those of the right to appeal, emphasizing their independence from one another. Additionally, a comparative analysis is conducted on various legal systems that have incorporated this right to a greater or lesser extent. Subsequently, through the study of the jurisprudence issued by the Constitutional Court, a contradictory and, to some extent, incomplete development is observed. However, at the same time, clear and forceful legal criteria regarding the nature of double conformity can be appreciated, thereby analyzing the jurisprudential evolution of this right. Finally, for the development of this academic work, research techniques and documentary observation methods were applied in the legal-doctrinal study and analysis of the subject matter and the rulings of the Constitutional Court. This research culminates in conclusions and recommendations that serve as a guide for the study of double conformity and its potential incorporation into the Ecuadorian legal system, fostering the strengthening of the criminal appeals system and advancing the collective legal knowledge on the subject.